Drinking patterns and risk behaviors associated with combined alcohol and energy drink consumption in college drinkers - Brache, K.; Stockwell, Tim (2011)
Objective: In recent years the consumption of alcohol mixed with energy drinks (AmED) has become popular in young adults in North America. There have been few studies into the drinking patterns and risk behaviors that accompany this new form of alcoholic beverage consumption and more information is required to support harm reduction and prevention efforts. This paper goes beyond previous research by investigating risk behaviors associated with AmED use while (1) controlling for risk-taking propensity, (2) examining a range of outcomes (e.g. stimulant drug use), and (3) replicating previous findings in a Canadian sample. Method: In winter 2009/10, a web-based survey was completed by 465 students (56% female) attending a university in Western Canada. Regression analyses were used to investigate whether consumption of AmED is associated with heavy drinking, stimulant drug use, and alcohol-related consequences. Results: A total of 105 students (23%) reported consuming AmED in the past 30. days. These students were more likely to be heavier drinkers, than non-AmED users after controlling for risk-taking propensity. More frequent AmED drinkers had twice the odds of experiencing one or more negative consequences from AmED use (e.g. drinking and driving, being hurt or injured), compared to less frequent drinkers after controlling for risk-taking propensity and drinking behavior. Conclusions: Students who consume AmED are at increased risk for harms. Therefore, consuming AmED should be considered "high-risk drinking" for university students and efforts should be made to discourage combined consumption.